A Novel Heterostructure Based on RuMo Nanoalloys and N‐doped Carbon as an Efficient Electrocatalyst for the Hydrogen Evolution Reaction. Issue 46 (15th October 2020) - Tu, Kejun; Tranca, Diana; Rodríguez‐Hernández, Fermín; Jiang, Kaiyue; Huang, Senhe; Zheng, Qi; Chen, Ming‐Xi; Lu, Chenbao; Su, Yuezeng; Chen, Zhenying; Mao, Haiyan; Yang, Chongqing; et al.
Abstract: Heterostructures exhibit considerable potential in the field of energy conversion due to their excellent interfacial charge states in tuning the electronic properties of different components to promote catalytic activity. However, the rational preparation of heterostructures with highly active heterosurfaces remains a challenge because of the difficulty in component tuning, morphology control, and active site determination. Herein, a novel heterostructure based on a combination of RuMo nanoalloys and hexagonal N‐doped carbon nanosheets is designed and synthesized. In this protocol, metal‐containing anions and layered double hydroxides are employed to control the components and morphology of heterostructures, respectively. Accordingly, the as‐made RuMo‐nanoalloys‐embedded hexagonal porous carbon nanosheets are promising for the hydrogen evolution reaction (HER), resulting in an extremely small overpotential (18 mV), an ultralow Tafel slope (25 mV dec −1 ), and a high turnover frequency (3.57 H2 s −1 ) in alkaline media, outperforming current Ru‐based electrocatalysts. First‐principle calculations based on typical 2D N‐doped carbon/RuMo nanoalloys heterostructures demonstrate that introducing N and Mo atoms into C and Ru lattices, respectively, triggers electron accumulation/depletion regions at the heterosurface and consequently reduces the energy barrier for the HER. This work presents a convenient method for rational fabrication of carbon–metal heterostructures for highly efficient electrocatalysis. Abstract : A novel heterostructure based on uniform RuMo nanoalloys and hexagonal N‐doped carbon nanosheets is prepared through a combination of hard template and anion‐exchange methods. The obtained material exhibits excellent electrocatalytic activity for the hydrogen evolution reaction. Theoretical calculation confirms that the heterosurfaces play a crucial role in accelerating the hydrogen evolution activity.